The level of Z-DNA in metabolically active, permeabilized mammalian cell nuclei is regulated by torsional strain (The Rockefeller University Press, 1989)
Permeabilized nuclei from mammalian cells encapsulated within agarose microbeads in an isotonic buffer are active in transcription and replication (Jackson, D. A., and P. R. Cook. 1985. EMBO (Eur. Mol. Biol. Organ.) J. 4:913-918). Their DNA is intact and the nuclei are accessible to macromolecules. Myeloma nuclei prepared in this way were used to probe the extent of DNA negative supercoiling and the effects of altering torsional strain by binding radioactively labeled monoclonal antibodies to Z-DNA. Control experiments used monoclonal antibodies against a nonhistone chromosomal protein, HMG-17. On increasing the amount of anti-HMG-17 added, a binding plateau was reached encompassing a 200-fold range of antibody concentration. On binding anti-Z-DNA antibody, a similar broad plateau of constant binding was found encompassing a 100-fold range of antibody concentration. The latter result was taken as a measure of preexisting Z-DNA in the nuclei. Additional anti-Z-DNA antibody binding can be "induced" in the presence of much higher concentration of antibody, apparently by perturbing the B-DNA/Z-DNA equilibrium. On inhibiting topoisomerase I with camptothecin, an elevated antibody binding plateau was found, suggesting that elastic torsional strain in the DNA is responsible for stabilizing the preexisting Z-DNA. This interpretation is supported by the fact that addition of small, nicking amounts of DNase I leads to a complete loss of antibody binding in the Z-DNA plateau region but not in the region of "induced" Z-DNA.